Vitamin E reduces TGF-beta2-induced changes in human trabecular meshwork cells - Yu, Alice L.; Moriniere, Jerome; Welge-Lussen, Ulrich (Current Eye Research, 2013)
To determine the effects of vitamin E on transforming growth factor-beta2 (TGF-?2)-induced cellular changes in cultured human trabecular meshwork (TM) cells.Human TM cells were pre-treated with different concentrations of vitamin E. Afterwards, cells were exposed to 1.0 ng/ml TGF-?2 for 24 h. Expressions of the heat shock protein ?B-crystallin, the extracellular matrix (ECM) component fibronectin and the ECM-degrading enzyme matrix metalloproteinase-2 (MMP-2) were examined by real-time polymerase chain reaction (PCR) analyses. The cytoskeleton was investigated by phalloidin staining.TGF-?2 increased the expressions of ?B-crystallin and fibronectin and reduced the levels of MMP-2. TGF-?2 induced the formation of actin stress fibers and cross-linked actin networks. Pre-treatment with different concentrations of vitamin E reversed the TGF-?2-induced cellular changes in cultured human TM cells.TGF-?2-mediated changes in human TM cells could be reduced by pre-treatment with vitamin E. Therefore, it may be speculated that increasing the antioxidative capacity may help to lower the incidence of characteristic glaucomatous changes in the TM.
EVALuna2:21137